2023
DOI: 10.1117/1.jbo.28.3.035001
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based optical approach for skin analysis of melanin and hemoglobin distribution

Abstract: Significance: Melanin and hemoglobin have been measured as important diagnostic indicators of facial skin conditions for aesthetic and diagnostic purposes. Commercial clinical equipment provides reliable analysis results, but it has several drawbacks: exclusive to the acquisition system, expensive, and computationally intensive.Aim: We propose an approach to alleviate those drawbacks using a deep learning model trained to solve the forward problem of light-tissue interactions. The model is structurally extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In our previous research, 22 we employed the skin decomposition principle from the field of computer graphics 23 research, 25 we confirmed that applying ground truth for the pigments could further improve performance. However, given the considerable usability benefits of using the optical method in place of the ground truth, we chose not to use ground truth for the pigments in this study.…”
Section: Pigment Discrimination Modelmentioning
confidence: 59%
See 1 more Smart Citation
“…In our previous research, 22 we employed the skin decomposition principle from the field of computer graphics 23 research, 25 we confirmed that applying ground truth for the pigments could further improve performance. However, given the considerable usability benefits of using the optical method in place of the ground truth, we chose not to use ground truth for the pigments in this study.…”
Section: Pigment Discrimination Modelmentioning
confidence: 59%
“…In our previous research, 22 we employed the skin decomposition principle from the field of computer graphics 23 to train a skin analysis model for dermatological research. From general skin images, this model produces four outputs: melanin, hemoglobin, shading, and specular maps, and yields results comparable to those of clinical diagnostic equipment.…”
Section: Methodsmentioning
confidence: 99%
“…The VISIA‐CR skin test can quickly and easily collect images with high definition and contains a variety of polarized light, which can evaluate the changes of acne in many aspects. Among them, the RBX‐red technology can detect the content of hemoglobin from cross‐polarized images, 32,33 and reflect the changes related to blood vessels and the degree of inflammation. Dermoscopy and VISIA‐CR skin examination were used to detect the images of the model and clinical pustular lesions.…”
Section: Discussionmentioning
confidence: 99%